Peran Hidden Curriculum dalam Mengatasi Ketidaksinkronan Kolaborasi Keluarga–Sekolah dalam Pembentukan Karakter - Hanunah Sofiatul Laily (Visionaria: Journal of Educational Innovation Management, 2026)
Character education in faith-based educational institutions, particularly Madrasah Aliyah, requires aligned collaboration between families and educational institutions. However, empirical practices indicate a lack of value alignment, resulting in inconsistencies in students’ character formation. This study aims to analyze the role of the hidden curriculum in aligning family–school collaboration and to formulate a collaboration model based on the hidden curriculum. The study employs a qualitative approach with a case study design. The research subjects include institutional administrators, teachers, parents, and students. Data collection techniques consist of in-depth interviews, participant observation, and documentation, while data analysis follows the interactive model of Miles and Huberman. The findings reveal that the hidden curriculum plays a significant role through role modeling, habituation, informal interaction, and the establishment of a consistent institutional culture, thereby facilitating value alignment across environments. This study produces five collaboration models: integrated role modeling, sustainable habituation, cultural alignment, informal educational interaction, and value continuity. The novelty of this research lies in the formulation of a collaboration model based on latent mechanisms as an alternative to structural approaches. The implications indicate that effective collaboration requires the integration of value-based practices rather than merely formal communication, leading to strengthened and sustainable character internalization.